Development of Ethnopedagogy-Based Reference Books on Mendut Temple Reliefs Vertebrate Sub-Materials - Nadia Dwi Cahyawati; Ika Sukmawati; Setiyo Prajoko (Indonesian Journal of Biology Education, 2023)
Mendut Temple as one of the historical heritages of Buddhist temple is located in Mendut Village, Mungkid District, Magelang Regency. In addition to its beautiful and sturdy visuals, Mendut Temple holds many moral messages through fable stories carved on the temple walls, namely Pancatantra and Boddhisattva Reliefs. From the reliefs, Mendut Temple has great potential as a learning resource in the form of a reference book. This research aims to produce a product in the form of a reference book on the identification of fauna reliefs and analyze the feasibility of the book based on material and media aspects. This research is designed as Research and Development (R&D) research with the ADDIE development model, this model includes Analysis, Design, Development, Implementation, and Evaluation. This research is limited to the development stage. Data collection was carried out by observing the fauna found in the reliefs of Mendut Temple. Analyzing the feasibility of the book using a modification of Sugiyono, namely through a validation sheet for the feasibility of the book adapted by BSNP. The results of the study found as many as 3 classes of vertebrate animals including Aves with 7 orders, Reptiles with 3 orders, and Mammals with 6 orders. The material expert validator's assessment of the developed reference book was 97.82%, for media experts it was 98%. The biology teacher's response to the reference book was 96.25% and the student response was 88.09%. This shows that the reference book developed is very feasible to get used